Optimalisasi Pengelolaan Website Desa dalam Menunjang Percepatan Pelayanan Digital di Desa Kualu Nenas - alkahfi, khairiah (Fakultas Teknik, Universitas Bangka Belitung, 2023)
To realize e-government through digital services, technology cannot be separated from technology. The government provides the New-Generation Village and Area Information System (Sideka-NG) application, an application that is already based on cloud computing (cloud) where village operators can follow data about their village finances services to the community online, create village websites. However, the management of the Kualu Pineapple village website is not optimal. Therefore, this service activity aims to help optimize website management in supporting the acceleration of digital services in Kualu Nenas Village. There are three stages that are passed starting from the planning, implementation to evaluation stages. The result of this activity is the optimization of making articles and village data into the website so that the website is upate and improves website SEO so that previously the website could not be found in the search system and had to type the full web address to appear on the initial homepage of the website when only mentioning the keyword Kualu Nenas. It is expected that in the future the website will be updated regularly and digital services will be carried out soon.